Hypercholesterolemia reduces the expression and function of hepatic drug metabolizing enzymes and transporters in rats. (1st July 2022) - Xu, Yuan; Lu, Jian; Guo, Yuanqing; Zhang, Yuanjin; Liu, Jie; Huang, Shengbo; Zhang, Yanfang; Gao, Liangcai; Wang, Xin
Abstract: Hypercholesterolemia, one of the most common lipid metabolic diseases, may cause severe complications and even death. However, the effect of hypercholesterolemia on drug-metabolizing enzymes and transporters remains unclear. In this report, we established a rat model of diet-induced hypercholesterolemia. Quantitative real-time PCR and Western blot analysis were used to study the mRNA and protein expression of drug-metabolizing enzymes and transporters. The functions of these enzymes and transporters were evaluated by the cocktail assay. In hypercholesterolemic rats, the expression of phase I enzymes (CYP1A2, CYP2C11, CYP2E1, CYP3A1/2, CYP4A1 and FMO1/3) and phase II enzymes (UGT1A1/3, PROG, AZTG, SULT1A1, NAT1 and GSTT1) decreased. In addition, the mRNA levels of drug transporter Slco1a1/2, Slco1b2, Slc22a5, Abcc2, Abcb1a and Abcg2 decreased in rats with hypercholesterolemia, while Abcb1b and Abcc3 increased. The decreased expression of hepatic phase I and II enzymes and transporters may be caused by the changes of CAR, FXR, PXR, and Hnf4α levels. In conclusion, diet-induced hypercholesterolemia changes the expression and function of hepatic drug-metabolizing enzymes and transporters in rats, thereby possibly affecting drug metabolism and pharmacokinetics. In clinical hyperlipidemia, patients should strengthen drug monitoring to avoid possible drug exposure mediated risks. Graphical Abstract: ga1 Highlights: The expression and activity of drug metabolizing enzymes (DME) decreased significantly in hypercholesterolemic rats. The mRNA expression of drug transporters changed in hypercholesterolemic rats. The decreased expression of DME and transporters may be caused by the changes of CAR, FXR, PXR, and Hnf4α . Hypercholesterolemia changes the expression and function of DME and transporters in rats.